Ultrastructure and secretion of glandular trichomes in species of subtribe Cajaninae Benth (Leguminosae, Phaseoleae) (vol 256, pg 431, 2019) - De Vargas, Wanderleia [UNESP] (2019)
Univ Estadual Paulista, Inst Biociencias, Programa Posgrad Ciencias Biol Bot, Dept Bot,Inst Biociencias, BR-18618000 Botucatu, SP, Brazil